Fabrication and Characterization of Porous Nanohydroxyapatite/ Chitosan-Cellulose Composite Scaffold for Biomedical Application (Global Journal of Medical Research, 2021)
Abstract not found
Keywords: bone grafting; scaffolds; hydroxyapatite; ofloxacin; chitosan